Robot-assisted laparoscopic ureteral reconstruction for ureter endometriosis: Case series and literature review. Issue 3 (March 2020) - Hung, Zhi-Chen; Hsu, Tzu-Hsiang; Jiang, Ling-Yu; Chao, Wei-Ting; Wang, Peng-Hui; Chen, Wei-Jen; Huang, Eric Yi-Hsiu; Chen, Yi-Jen; Lin, Alex T. L.
Abstract : Background: The aim of this report was to review experience from a single hospital in treating ureteral obstruction related to endometriosis with robot-assisted laparoscopic ureteral reconstruction. Methods: This retrospective analysis study (Canadian Task Force classification II-3) was conducted at an academic tertiary hospital. Five female patients with hydronephrosis without significant elevation of serum creatinine levels were enrolled. Ureteral endometriosis with obstruction was suspected on radiological images. Previous treatment with double-J stenting with or without medical treatment had failed in all of the patients. We performed robot-assisted laparoscopic segmental resection for ureteral endometriosis and reconstructed the ureter through ureteroureterostomy (RUU) or ureteroneocystostomy (RUC). The involved ureters included left lower ureter in three patients and right lower ureter in two patients. RUU was performed in four patients and RUC in one patient. All of the operations were completed smoothly without complications. Results: All ureteral endometrioses were successfully resected, and follow-up sonography or intravenous pyelography showed resolution of hydronephrosis in all of the patients. Conclusion: Our experience proves the feasibility and efficacy of a robot-assisted approach for this rare situation with good outcomes.